What factors affect patient access and engagement with clubfoot treatment in low‐ and middle‐income countries? Meta‐synthesis of existing qualitative studies using a social ecological model. Issue 5 (10th March 2016) - Drew, Sarah; Lavy, Christopher; Gooberman‐Hill, Rachael
Abstract: Objectives: To conduct a systematic synthesis of previous research to identify factors that affect treatment‐seeking for clubfoot and community‐level interventions to improve engagement in low‐ and middle‐income counties. Methods: A search of five databases was conducted, and articles screened using six criteria. Quality was appraised using the Critical Appraisal Skills Programme checklist. Eleven studies were identified for inclusion. Analysis was informed by a social ecological model, which specifies five inter‐related factors that may affect treatment‐seeking: intrapersonal, interpersonal, institutional, community or socio‐cultural factors and public policy. Results: Intrapersonal barriers experienced were a lack of income and additional responsibilities. At the interpersonal level, support from fathers, the extended family and wider community affected on treatment‐seeking. Institutional or organisational factors included long distances to treatment centres, insufficient information about treatments and challenges following treatment. Guardians' beliefs about the causes of clubfoot shaped behaviour. At the level of public policy, two‐tiered healthcare systems made it difficult for some groups to access timely care. Interventions to address these challenges included counselling sessions, outreach clinics, brace recycling and a range of education programmes. Conclusions: This study identifies factors that affect access and engagement with clubfoot treatment across diverse settings and strategies to address them.